2018
DOI: 10.1016/j.canlet.2018.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of edelfosine encapsulated lipid nanoparticles causes regression of lung metastases in pre-clinical models of osteosarcoma

Abstract: Osteosarcoma (OS) is the most frequent paediatric bone cancer, responsible for 9% of all cancer-related deaths in children. In this paper, a new strategy based on delivering edelfosine (ET) in lipid nanoparticles (LN) was explored in order to target the primary tumour and eliminate metastases. The in vitro and in vivo efficacy of the free drug, drug loaded into lipid nanoparticles (ET-LN) and doxorubicin (DOX) against osteosarcoma (OS) cells was analysed. ET and ET-LN decreased the growth of OS cells in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Moreover, functional drug delivery system can also re-educate the tumor environment which involves tumor cells, immune cells, stomal cell, etc., to block the initiation of metastasis 125-128. Recently, edelfosine (ET), a potential anti-tumor agent with poor oral bioavailability and severe side effects, was encapsulated in lipid nanoparticles (ET-LNs) for osteosarcoma treatment by Gonzalez-Fernandez et al 126. Results of this study demonstrate that orally administered ET-LNs show significant growth inhibition effects in primary osteosarcoma cells.…”
Section: Strategies For Osteosarcoma-targeted Drug Deliverymentioning
confidence: 83%
“…Moreover, functional drug delivery system can also re-educate the tumor environment which involves tumor cells, immune cells, stomal cell, etc., to block the initiation of metastasis 125-128. Recently, edelfosine (ET), a potential anti-tumor agent with poor oral bioavailability and severe side effects, was encapsulated in lipid nanoparticles (ET-LNs) for osteosarcoma treatment by Gonzalez-Fernandez et al 126. Results of this study demonstrate that orally administered ET-LNs show significant growth inhibition effects in primary osteosarcoma cells.…”
Section: Strategies For Osteosarcoma-targeted Drug Deliverymentioning
confidence: 83%
“…Perhaps, it would be of interest to perform these experiments in a tumor model that is more sensitive to the action of EF. For instance, orally administered EF loaded into solid lipid nanoparticles proved to be very efficacious in an HOS (ATCC ® CRL-1543™) orthotopic tumor model [ 35 ], although the EF IC 50 value in this cell line was 2.72 µM instead of 59 µM in the P1.15 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, González-Fernández et al have reported the combination of DOX and EDL and demonstrated synergistic effect in osteosarcoma cells; however, the study was limited to in vitro conditions. 25 In the present study, we have explored a detailed in vivo therapeutic efficacy in xenograft model and established the toxicity profile of free drugs and the nanoparticle-based combination.…”
Section: Introductionmentioning
confidence: 99%